Ten Years of Product Market Reform in OECD Countries Insights from a Revised PMR Indicator - Wölfl, Anita (OECD Publishing, 2009)
This paper describes patterns and developments of regulation that potentially affect product market competition in OECD countries over the past decade. It uses the 2008 update and revision of the OECD indicators of product market regulation (PMR) that integrate to a larger extent than in the past information on sector-specific regulation and adapt a simpler and more transparent aggregation technique. The results show that OECD countries have extensively liberalised product markets over the past ten years and - as a consequence - convergence of regulation across OECD countries can be observed. However, reforms appear to have slowed in the most recent period (2003-2008) as compared with the earlier period (1998- 2003). Easing of product market regulation appears to have been driven to a considerable extent by reforms in sector-specific regulation, notably as regards the gas, electricity and telecommunications markets. Countries appear also to have followed consistent reform approaches. However, scope for further reform remains, especially as regards controls of governments over businesses, and as regards certain sectors such as professional services and retail trade
Keywords: Economics